1999
DOI: 10.1088/0022-3727/32/8/012
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of streamer propagation in air

Abstract: Results concerning the dynamics of streamer propagation in air under a uniform electric field are presented and discussed. Experiments were performed in a plane-parallel electrode arrangement with positive streamers initiated at a sharp point in the earthed anode. The basic properties of streamers are described in terms of the electric field required for a stable propagation and the associated propagation velocity. Critical parameters are the ambient electric field, the voltage used for streamer initiation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
56
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 4 publications
(8 reference statements)
9
56
0
1
Order By: Relevance
“…The propagation velocity of the ionization front is in the range of 3 × 10 7 to 4 × 10 7 cm/s. We find that the calculated values for the frontal velocities agree well with the experimental results [21][22][23] and with those reported in [20,[24][25][26][27]. Measurements [21,22] of the average propagation velocity of the ionization front extend from 2 × 10 7 to 5 × 10 7 cm/s, the propagation average velocity [24,25] of the ionization wave is approximately of 5 × 10 7 cm/s, which agrees with our results.…”
Section: Resultssupporting
confidence: 91%
“…The propagation velocity of the ionization front is in the range of 3 × 10 7 to 4 × 10 7 cm/s. We find that the calculated values for the frontal velocities agree well with the experimental results [21][22][23] and with those reported in [20,[24][25][26][27]. Measurements [21,22] of the average propagation velocity of the ionization front extend from 2 × 10 7 to 5 × 10 7 cm/s, the propagation average velocity [24,25] of the ionization wave is approximately of 5 × 10 7 cm/s, which agrees with our results.…”
Section: Resultssupporting
confidence: 91%
“…However, when the pulse duration is below the certain value, the impact ionization is week, therefore, the streamer may stop some place in the gap. Allen found that long pulse duration also caused low stability propagation field E st in the experiment [4].…”
Section: Effect Of the Pulse Voltagementioning
confidence: 87%
“…The experiment on steamer dynamics is based on the 3-electrode arrangement [4] which consists of two paralleled plane electrodes with a gap clearance of about 12cm, as figure 1 shows. The upper plane is applied with a variable negative voltage, while the nether plane is grounded, establishing a quasi-uniform electric field between the two planes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations